The Erosion of Threatened Southern Mountain Caribou Migration - Clayton T. Lamb; Robin Steenweg; Robert Serrouya; Dave Hervieux; R. Scott McNay; Douglas C. Heard; Bruce N. McLellan; Carolyn Shores; Eric Palm; Line Giguere; Jake Hubner; Jean Polfus; et al. (Global Change Biology, 2025)
Migration enables animals to access seasonally and spatially varying resources, resulting in greater abundance compared to analogous non‐migratory wildlife. Both Western science and Indigenous knowledge recognize the critical role of migration in sustaining wildlife; yet these movements are increasingly disrupted by human activity worldwide. Despite their importance, long‐term changes in migratory patterns for large mammals remain challenging to quantify. Therefore, to address this gap, we analyzed 35 years (1987–2022) of telemetry data for southern mountain caribou ( n = 2967 animal‐years), a threatened population that typically exhibits two main types of annual migration. The first type is a single horizontal migration between summer and winter ranges, while the second is a twice‐per‐year vertical migration between high and low elevations. We studied the extent and type of migration, changes through time, and determined if these changes correlated with landscape disturbance or shifts in weather. Our results show that caribou reduced their migratory duration (2–3 days/decade), distance (6–8 km/decade or 15%–25%) and elevation change (120–150 m/decade or 7%–23% for elevational migrants). The subpopulations of caribou adapted to extreme snow depths conducted a unique elevational migration twice a year, which is globally distinctive among ungulates. However, this elevational migration is diminishing in distance and elevation. The changes in elevational and horizontal migration correlated with increased human disturbance, especially of low‐elevation winter ranges. Changes in weather did not appear to be a major driver of the migratory declines. Declines in migratory behaviour occurred concomitantly with population declines and increases in disturbance, and these processes are likely intertwined. The rapid loss of these unique migrations is a significant conservation concern that could have irreversible consequences for the social transmission of fitness‐maximizing behaviors.

Rerouting of a major shipping lane through important harbour porpoise habitat caused no detectable change in annual occurrence or foraging patterns - Kylie Owen; Julia Carlström; Pia Eriksson; Mathias Andersson; Robin Nordström; Emilia Lalander; Signe Sveegaard; Line A. Kyhn; Emily T. Griffiths; Mel Cosentino; Jakob Tougaard (Marine Pollution Bulletin, 2024)

Corrigendum - CLARE D. MARSDEN; ROSIE WOODROFFE; MICHAEL G. L. MILLS; J. WELDON MCNUTT; SCOTT CREEL; ROSEMARY GROOM; MASENGA EMMANUEL; SARAH CLEAVELAND; PIETER KAT; GREGORY S. A. RASMUSSEN; JOSHUA GINSBERG; ROBIN LINES; et al. (Molecular Ecology, 2012)

Spatial and temporal patterns of neutral and adaptive genetic variation in the endangered African wild dog ( Lycaon pictus ) - CLARE D. MARSDEN; ROSIE WOODROFFE; MICHAEL G. L. MILLS; J. WELDON McNUTT; SCOTT CREEL; ROSEMARY GROOM; MASENGA EMMANUEL; SARAH CLEAVELAND; PIETER KAT; GREGORY S.A. RASMUSSEN; JOSHUA GINSBERG; ROBIN LINES; et al. (Molecular Ecology, 2012)
Deciphering patterns of genetic variation within a species is essential for understanding population structure, local adaptation and differences in diversity between populations. Whilst neutrally evolving genetic markers can be used to elucidate demographic processes and genetic structure, they are not subject to selection and therefore are not informative about patterns of adaptive variation. As such, assessments of pertinent adaptive loci, such as the immunity genes of the major histocompatibility complex (MHC), are increasingly being incorporated into genetic studies. In this study, we combined neutral (microsatellite, mtDNA) and adaptive (MHC class II DLA‐DRB1 locus) markers to elucidate the factors influencing patterns of genetic variation in the African wild dog ( Lycaon pictus ); an endangered canid that has suffered extensive declines in distribution and abundance. Our genetic analyses found all extant wild dog populations to be relatively small ( N e